CUTANEOUS SQUAMOUS CELL CARCINOMA IN CHILDREN - Georgiana-Cristina Ionescu; Zamfir-Radu Ionescu (Amaltea Medical Publishing House, 2015)
The article objective consists in approaching a rare condition in children, the cutaneous squamous cell carcinoma (cSCC), whose frequency may become higher due to risk factors accumulation. Analyzing the few data furnished trough available scientific literature, centered mainly on adult pathology, there have been outlined required data for the pediatric diagnosis and treatment of cSCC. Therefore, adopting a proper management for children particularities becomes a necessity.